Synergistic electrochemical sensing of 2,4-dinitrotoluene via bimetallic nickel-cobalt oxide nanoparticles - Bharti Sharma; Shikha Jain; Ahmad Umar; Sushma Rani; Sandeep Kumar; Ahmed A. Ibrahim; Neeraj Dilbaghi (Chemical Physics Impact, 2024)
This study presents a comprehensive investigation into the synthesis, characterization, and application of an exceptionally sensitive electrochemical sensor designed for the ultrasensitive detection of 2,4-dinitrotoluene (DNT), a notorious explosive compound. The sensor employs bimetallic nickel-cobalt oxide (NiCo2O4) nanoparticles, synthesized through a facile hydrothermal method. Extensive analytical techniques, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), and x-ray photoelectron spectroscopy (XPS), were employed to validate the crystallinity and purity of the NiCo2O4 nanoparticles. These nanoparticles, possessing remarkable properties, form the core of our electrochemical sensor, enabling it to offer heightened sensitivity and selectivity even under ambient conditions. Most notably, this sensor boasts an impressively low limit of detection (LOD) of 18 nM, coupled with a broad linear detection range (LDR) spanning from 10 nM to 100 nM. The sensor exhibits robust sensitivity, excellent selectivity, and an outstandingly low detection threshold, collectively demonstrating its potential for precise and accurate detection of DNT. This research underscores the significant potential of bimetallic oxide nanoparticles, specifically NiCo2O4, in the precise quantification of nitro-aromatic analytes. This study opens up promising avenues for assessing hazardous compounds in complex environmental matrices, thereby contributing to the advancement of electrochemical sensing. Additionally, this novel sensing platform holds substantial promise for enhancing security measures and environmental monitoring through its improved sensitivity and selectivity in the detection of explosives.